3D1D hydro-nucleosynthesis simulations – I. Advective–reactive post-processing method and its application to H ingestion into He-shell flash convection in rapidly accreting white dwarfs. Issue 1 (20th February 2021) - Stephens, David; Herwig, Falk; Woodward, Paul; Denissenkov, Pavel; Andrassy, Robert; Mao, Huaqing
ABSTRACT: We present two mixing models for post-processing of 3D hydrodynamic simulations applied to convective–reactive i -process nucleosynthesis in a rapidly accreting white dwarf (RAWD) with [Fe/H] = −2.6, in which H is ingested into a convective He shell. A 1D advective two-stream model adopts physically motivated radial and horizontal mixing coefficients constrained by 3D hydrodynamic simulations. A simpler approach uses diffusion coefficients calculated from the same simulations. All 3D simulations include the energy feedback of the 12 C( p, γ) 13 N reaction from the H entrainment. Global oscillations of shell H ingestion in two of the RAWD simulations cause bursts of entrainment of H and non-radial hydrodynamic feedback. With the same nuclear network as in the 3D simulations, the 1D advective two-stream model reproduces the rate and location of the H burning within the He shell closely matching the 3D simulation predictions, as well as qualitatively displaying the asymmetry of the X H profiles between the upstream and downstream. With a full i -process network the advective mixing model captures the difference in the n-capture nucleosynthesis in the upstream and downstream. For example, 89 Kr and 90 Kr with half-lives of 3.18 min and 32.3 s differ by a factor 2–10 in the two streams. In this particular application the diffusion approach provides globally the same abundance distribution as the advective two-stream mixing model. The resulting i -process yields are in excellent agreement with observations of the exemplary CEMP-r/s star CS31062-050.